Development of policies for a digital repository for a higher education institution with technological disadvantages - José Alonso Fernández López; María Manuela Pintor Chávez; Marcela Georgina Gómez Zermeño (Arizona State University, 2016)
This study presents a qualitative cross-sectional analysis about the conditions of an educational center of higher education in disadvantaged conditions due to the geographic isolation and lack of technological infrastructure and internet access. To reduce this information access gap, it is proposed to implement a repository of learning objects, taking into account the needs of the institution. Through the use of interviews, information was gathered on the experiences and perspectives of students, teachers and principals about the use and adoption of a repository of learning objects. The results show that the participants have positive opinion about the implantation of a virtual repository; the policies derived from this research are shown. However, the process must continue to develop in relation to the election and creation of the content to determine if it contributes positively to the teaching and learning processes.